Links between Dietary Protein Sources, the Gut Microbiota, and Obesity - Madsen, Lise; Myrmel, Lene S.; Fjære, Even; Liaset, Bjørn; Kristiansen, Karsten (Frontiers in Physiology, 2017)
The association between the gut microbiota and obesity is well documented in both humans and in animal models. It is also demonstrated that dietary factors can change the gut microbiota composition and obesity development. However, knowledge of how diet, metabolism and gut microbiota mutually interact and modulate energy metabolism and obesity development is still limited. Epidemiological studies indicate an association between intake of certain dietary protein sources and obesity. Animal studies confirm that different protein sources vary in their ability to either prevent or induce obesity. Different sources of protein such as beans, vegetables, dairy, seafood and meat differ in amino acid composition. Further, the type and level of other factors, such as fatty acids and persistent organic pollutants vary between dietary protein sources. All these factors can modulate the composition of the gut microbiota and may thereby influence their obesogenic properties. This review summarizes evidence of how different protein sources affect energy efficiency, obesity development and the gut microbiota, linking protein-dependent changes in the gut microbiota with obesity.